INTER-SECTORAL INTEGRATION AND GROWTH DYNAMICS IN THE REGIONAL ECONOMY: THE EXAMPLE OF THE REGIONS OF UZBEKISTAN - Avzaljon Umarov (International Scientific and Current Research Conferences, 2025)
This study investigates how inter-sectoral integration shapes growth dynamics across Uzbekistan’s regions. Building a regional input–output framework, complemented by Location Quotients, network analysis, and spatial econometrics, it assesses how sector linkages translate into diversified and resilient regional growth. Using reconstructed region-level IO tables and time-series regional data, we find that stronger backward linkages from agro-processing and robust forward linkages into logistics, services, and construction are associated with faster regional growth and greater diversification. Regional heterogeneity matters: Fergana’s agro-processing, Navoi/Karakalpakstan’s downstream activities, Samarkand/Bukhara’s tourism linkages, and Tashkent’s services-driven diffusion. Policy implications emphasize value chains, infrastructure, human capital, and cross-sector collaboration.